INTERNATIONAL RELATIONS AND THE INTER-AMERICAN SYSTEM OF HUMAN RIGHTS PROMOTION AND PROTECTION. STRATEGIC EXPLOITATION OF WINDOWS OF OPPORTUNITY - Thede, Nancy; Brisson, Hughes (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2011)
Given the asymmetrical nature of international relations in the western hemisphere throughout the history of the OAS, we postulate that the dynamic of those relations explains major developments within the Inter-American human rights system, whereas the reverse is not the case. In other words, the system, its norms and constraints, have influenced little the direction of relations amongst states in the Americas. An historical overview reveals however that the system has consistently shown itself able to exploit “windows of opportunity” to push back the frontiers of its institutional limits, but this ability to impose more stringent human rights norms is never entirely unquestioned and remains highly contested by the member states. The article uses a periodisation of relations in the hemisphere on the one hand, and those within the inter-American system, on the other. It then analyses the periods that show strong correlation between international relations and innovations within the system in order to identify trends and perspectives for the future. It concludes with three possible scenarios for the immediate future of the system, based on emerging trends in international relations.